mRNA Display Using Covalent Coupling of mRNA to Translated Proteins - Wang, Rong (Methods Mol Biol, 2012)
mRNA display is a powerful technique that allows for covalent coupling of a translated protein with its coding mRNA. The resulting conjugation between genotype and phenotype can be used for the efficient selection and identification of peptides or proteins with desired properties from an mRNA-displayed peptide or protein library with high diversity. This protocol outlines the principle of mRNA display and the detailed procedures for the synthesis of mRNA-protein fusions. Some special considerations for library construction, generation and purification are discussed.